Experimental Testing and Numerical Modelling of Thermal Runaway in 18650 Lithium-Ion Batteries - Pretorius, Lourens Badenhorst (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2026.